Onset of secondary progressive multiple sclerosis is not influenced by current relapsing multiple sclerosis therapies - Coret, Francisco (Mult Scler J Exp Transl Clin, 2018)
BACKGROUND: Disease-modifying therapies are thought to reduce the conversion rate to secondary progressive multiple sclerosis. OBJECTIVE: To explore the rate, chronology, and contributing factors of conversion to the progressive phase in treated relapsing–remitting multiple sclerosis patients. METHODS: Our study included 204 patients treated for relapsing–remitting multiple sclerosis between 1995 and 2002, prospectively followed to date. Kaplan–Meier analysis was applied to estimate the time until secondary progressive multiple sclerosis conversion, and multivariate survival analysis with a Cox regression model was used to analyse prognostic factors. RESULTS: Relapsing–remitting multiple sclerosis patients were continuously treated for 13 years (SD 4.5); 36.3% converted to secondary progressive multiple sclerosis at a mean age of 42.6 years (SD 10.6), a mean time of 8.2 years (SD 5.2) and an estimated mean time of 17.2 years (range 17.1–18.1). A multifocal relapse, age older than 34 years at disease onset and treatment failure independently predicted conversion to secondary progressive multiple sclerosis but did not influence the time to reach an Expanded Disability Status Scale of 6.0. CONCLUSIONS: The favourable influence of disease-modifying therapies on long-term disability in relapsing–remitting multiple sclerosis is well established. However, the time to progression onset and the subsequent clinical course in treated patients seem similar to those previously reported in natural history studies. More studies are needed to clarify the effect of disease-modifying therapies once the progressive phase has been reached.